A Note on Non-Negative Singular Infinity-Harmonic Functions in the Half-Space - Bhattacharya, Tilak (Revista Matemática Complutense, 2005)
In this work we study non-negative singular infinity-harmonic functions in the half-space. We assume that solutions blow-up at the origin while vanishing at infinity and on a hyperplane. We show that blow-up rate is of the order |x|−1/3.